Deposition and Characterization of Cu-Enhanced High-Entropy Alloy Coatings via DC Magnetron Sputtering - Arcadii Sobetkii; Laurentiu-Florin Mosinoiu; Stefania Caramarin; Dumitru Mitrica; Laura-Madalina Cursaru; Alexandru-Cristian Matei; Ioan-Albert Tudor; Beatrice-Adriana Serban; Mihai Ghita; Nicoleta Vitan; Julia Witt; Ozlem Ozcan; et al. (Applied Sciences)
Protection against microbiologically influenced corrosion (MIC) is critical for materials used in aquatic environments, as MIC accelerates material degradation and leads to faster structural failure. Copper (Cu) has the potential to substantially improve the MIC resistance in alloys. In this study, high-entropy alloy (HEA) coatings containing Cu were deposited using DC (Direct Current) magnetron sputtering to enhance the corrosion resistance and mechanical properties of various substrates. Two CuCrFeMnNi HEA compositions in the form of bulk alloys and PVD (Physical Vapor Deposition) coatings, with 5% and 10% Cu, were analyzed for their microstructural, mechanical, and anticorrosive characteristics. Deposition parameters were varied to select the optimal values. Microstructural evaluations using SEM-EDS (scanning electron microscopy and energy dispersive X-ray spectroscopy), XRD (X-ray diffraction), and AFM (atomic force microscopy) revealed uniform, dense coatings with good adhesion composed of dendritic and interdendritic BCC (body-centered cubic) and FCC (face centered cubic) structures, respectively. Microhardness tests indicated improved mechanical properties for the samples coated with developed HEAs. The coatings exhibited improved corrosion resistance in NaCl solution, the 10% Cu composition displaying the highest polarization resistance and lowest corrosion rate. These findings suggest that Cu-containing HEA coatings are promising candidates for applications requiring enhanced corrosion protection.